The Role of Physical Activity in the Aging Proces - Sieradocha, Kamila; Śledziewska, Aleksandra Maria; Cyrkler, Magdalena; Śluzek , Natalia; Karasiński, Maciej (Quality in Sport, 2025)
Aging is associated with a decline in physiological and cellular functions, leading to increased susceptibility to various chronic diseases, including cardiovascular, musculoskeletal, and metabolic disorders. As life expectancy rises, so does the need for effective strategies to mitigate the health challenges faced by older adults. Physical activity has emerged as a critical intervention, offering a wide range of benefits that address the multifaceted impacts of aging. This review explores the role of regular physical activity in enhancing health, preventing disease, and improving the overall quality of life in older adults. It highlights how exercise mitigates age-related declines in muscle strength, bone density, and cardiovascular health, while also reducing systemic inflammation and oxidative stress. Furthermore, the integration of physical activity into daily routines is shown to lower the risk of chronic conditions, improve cognitive function, and promote functional independence. Despite its benefits, barriers such as mobility issues, chronic illnesses, and limited accessibility to exercise programs hinder widespread adoption among aging populations. This review underscores the importance of tailored and accessible exercise interventions, as well as the need for further research to optimize physical activity guidelines and strategies. By prioritizing physical activity, society can empower older adults to lead healthier, more independent lives, ultimately transforming the aging process.